Implicit need for affiliation is associated with increased corrugator activity in a non-positive, but not in a positive social interaction - Kordik, Annette; Schultheiss, Oliver; Eska, Kathrin (Journal of research in personality, 2012)
Affective changes in response to motive-relevant stimuli are a defining feature of implicit motives. We therefore expected to find an effect of individual differences in the implicit need for affiliation (nAff) on corrugator supercilii activity, an indicator of affect, when participants were confronted with nonverbal indicators of a conversational partner’s withdrawal. Participants’ nAff was assessed with a Picture Story Exercise (PSE). They were then involved in an interaction with a smiling or a neutral experimenter while their corrugator activity was measured with electromyography (EMG). As expected, we found higher corrugator activity for people high in nAff compared to people low in nAff when the experimenter kept a neutral facial expression throughout the interaction but not when he/she was smiling.
Keywords: Implicit motives; Affiliation motive; EMG; Affect; Facial expressions of emotion; Neutral facial expression; Corrugator supercili